Efficacy of Endoscopic Sinus Surgery in the Treatment of Chronic Rhinosinusitis - Basílio, Flávia Machado Alves; Arantes, Murilo Carlini; Ballin, Annelyse Cristine; Dallagnol, Moises Rafael; Bornhausen, Mathias Bohn; Szkudlarek, Denilson Cavazzani; Santos, Marco César Jorge; Mocellin, Marcos (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: The endoscopic sinus surgery (FESS) is currently regarded as the gold standard in the treatment of chronic rhinosinusitis (RNSC), with or without nasal polyposis refractory to medical therapy optimized.Objective: To evaluate the improvement of symptoms after FESS RNSC, through a questionnaire.Method: This is a prospective study, which included 34 patients undergoing FESS during the year 2009, the Service of Otorhinolaryngology, Hospital das Clínicas / UFPR. Of these, 22 were diagnosed as RNSC RNSC and 12 had associated nasal polyps. All patients underwent a questionnaire on preoperative symptoms, comorbidities and degree of symptom improvement after surgery, six months after the procedure.Results: The percentage improvement of symptoms more prevalent in the group with RNSC was as follows: nasal obstruction 87.4%, 80.5% headache, pain / facial pressure 91.6% 81.2% posterior nasal discharge. In the group with polyposis associated improvement was nasal obstruction 76.6%, 76.6% posterior nasal discharge, hyposmia, 68.7%, headache 83%. In our study we found an overall improvement in symptoms of 83.74% in patients with RNSC and 80.5% in patients with associated nasal polyposis.Conclusion: FESS is highly effective in controlling symptoms of RNSC with or without polyposis and is, in our study, its efficacy similar to that found in the literature. With respect to patients with nasal polyposis, studies are needed with longer follow up, since this disease has a high degree of recurrence.
Keywords: sinusitis; symptoms; treatment outcome